Exploring the Association between Adolescents Participation in Sport and Their Attachment to Parent and Peer - Šukys, Saulius; Lisinskienė, Aušra (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2015)
This qualitative cross-sectional design study examine the association between adolescents’ participation in sports activities and their attachment with parents and peers. A total of 1348 (716 female and 632 male) aged 12 to 16 completed questionnaire assessing attachment with parent and peer (trust, communication, alienation). This study showed that adolescents not participating in sports scored significantly lower on all Parent Attachment subscales when compared to adolescent athletes. The research also revealed that participation in sports has an effect on both Trust in Peers and Alienation from them. Boys scored significantly higher than girls did on Trust and Alienation with parents, while girls scored significantly higher than boys in terms of Peer attachment. Younger adolescent scored significantly higher on the Parent Attachment scale whereas senior adolescents scored higher on Trust with Peer.